Role of bicarbonate/CO2 in the inhibition of Escherichia coli growth by cyanate. - Kozliak, E I (1995)
Cyanase is an inducible enzyme in Escherichia coli that catalyzes the reaction of cyanate with bicarbonate to give two CO2 molecules. The gene for cyanase is part of the cyn operon, which includes cynT and cynS, encoding carbonic anhydrase and cyanase, respectively. Carbonic anhydrase functions to prevent depletion of cellular bicarbonate during cyanate decomposition (the product CO2 can diffuse out of the cell faster than noncatalyzed hydration back to bicarbonate). Addition of cyanate to the culture medium of a delta cynT mutant strain of E. coli (having a nonfunctional carbonic anhydrase) results in depletion of cellular bicarbonate, which leads to inhibition of growth and an inability to catalyze cyanate degradation. These effects can be overcome by aeration with a higher partial CO2 pressure (M. B. Guilloton, A. F. Lamblin, E. I. Kozliak, M. Gerami-Nejad, C. Tu, D. Silverman, P. M. Anderson, and J. A. Fuchs, J. Bacteriol. 175:1443-1451, 1993). The question considered here is why depletion of bicarbonate/CO2 due to the action of cyanase on cyanate in a delta cynT strain has such an inhibitory effect. Growth of wild-type E. coli in minimal medium under conditions of limited CO2 was severely inhibited, and this inhibition could be overcome by adding certain Krebs cycle intermediates, indicating that one consequence of limiting CO2 is inhibition of carboxylation reactions. However, supplementation of the growth medium with metabolites whose syntheses are known to depend on a carboxylation reaction was not effective in overcoming inhibition related to the bicarbonate deficiency induced in the delta cynT strain by addition of cyanate. Similar results were obtained with a deltacyn strain (since cyanase is absent, this strain does not develop a bicarbonate deficiency when cyanate is added); however, as with the deltacynT strain, a higher partial CO(2) pressure in the aerating gas or expression of carbonic anhydrase activity (which contributes to a higher intercellular concentration of bicarbonate/CO(2)) significantly reduced inhibition of growth. There appears to be competition between cyanate and bicarbonate/CO(2) at some unknown but very important site such that cyanate binding inhibits growth. These results suggest that bicarbonate/CO(2) plays a significant role in the growth of E. coli other than simply as a substrate for carboxylation reactions and that strains with mutations in the cyn operon provide a unique model system for studying aspects of the metabolism of bicarbonate/CO(2) and its regulation in bacteria.